Risks in domestic banks' corporate lending business - Christoph Memmel; Christoph Roling (Deutsche Bundesbank, 2021)
We introduce an empirical approach to studying credit risk in the corporate loan portfolio. First, historical adverse scenarios for loss rates are identified at sector level. Second, we estimate the empirical association between loan losses and economic growth and then apply it to a scenario of adverse economic growth. We additionally model an increase in risk weights for banks that use an internal ratings-based approach (IRBA) to calculate the capital adequacy requirement for their loan portfolio. – – Es wird ein empirischer Ansatz vorgestellt, wie die Kreditrisiken im Unternehmenskreditportfolio untersucht werden können. Dabei werden Stress-Szenarien für Verlustquoten auf der Ebene der einzelnen Sektoren historisch ermittelt. Alternativ schätzen wir die empirische Assoziation zwischen Verlusten im Kreditgeschäft und dem Wirtschaftswachstum, wobei diese dann auf ein Szenario adversen Wirtschaftswachstums angewendet wird. Bei Banken, die die notwendige Eigenkapitalunterlegung im Kreditportfolio mit einem internen Ansatz bestimmen, modellieren wir zusätzlich einen Anstieg der Risikogewichte.
Keywords: C53; G01; G17; G21; 330; Credit Risk; Default Rate; Stress Test